ROHINGYA MINORITY IN MYANMAR BETWEEN THE RELIGIOUS PERSECUTION AND THE REALITY OF CONSTITUTIONAL PROTECTION. - Driss, Bakhouya (Faculty of Law, Universitas Brawijaya, 2016)
The government's performance in the State of Myanmar raises questions about the reality of its position on what is happening to the range of its citizens who are Muslims Alrohengjian, it bear full responsibility for the protection and preservation of their rights. Despite the government's signing of Myanmar on the international agreements and conventions on human rights, despite its stated commitment to the protection of human rights and the promotion of democracy and the rule of law; the government has not taken any real action to protect the Rohingyas and address violence or stop racist policy of ethnic cleansing, which govern the Muslims of Rohingya by Buddhist extremists. We will discuss in this paper what is really happening to the Muslims Alrohengjian in Myanmar, especially in the recent wave of persecution and ethnic cleansing against them, and we are exposed to historical backgrounds of these crimes and the role of internal constitutional provisions and the provisions of international conventions on the protection of this vulnerable minority